Genome sequence of the opportunistic human pathogen Magnusiomyces capitatus - Brejová, Bronislava; Lichancová, Hana; Brázdovič, Filip; Hegedűsová, Eva; Forgáčová Jakúbková, Michaela; Hodorová, Viktória; Džugasová, Vladimíra; Baláž, Andrej; Zeiselová, Lucia; Cillingová, Andrea; Neboháčová, Martina; Raclavský, Vladislav; et al. (Current genetics, 2019)
The yeast Magnusiomyces capitatus is an opportunistic human pathogen causing rare yet severe infections, especially in patients with hematological malignancies. Here, we report the 20.2 megabase genome sequence of an environmental strain of this species as well as the genome sequences of eight additional isolates from human and animal sources providing an insight into intraspecies variation. The distribution of single-nucleotide variants is indicative of genetic recombination events, supporting evidence for sexual reproduction in this heterothallic yeast. Using RNAseq-aided annotation, we identified genes for 6518 proteins including several expanded families such as kexin proteases and Hsp70 molecular chaperones. Several of these families are potentially associated with the ability of M. capitatus to infect and colonize humans. For the purpose of comparative analysis, we also determined the genome sequence of a closely related yeast, Magnusiomyces ingens. The genome sequences of M. capitatus and M. ingens exhibit many distinct features and represent a basis for further comparative and functional studies.
Keywords: multigenová rodina; Antifungal Agents; rekombinace genetická; genomika; Mycoses; Virulence Factors; Genome, Fungal; fylogeneze; Humans; výpočetní biologie; Opportunistic Infections; Phenotype; Phylogeny; Saccharomycetales; Computational Biology; Microbial Sensitivity Tests; Molecular Sequence Annotation; lidé; fenotyp; oportunní infekce; Recombination, Genetic; antifungální látky; mikrobiální testy citlivosti; anotace sekvence; faktory virulence; genom fungální; mykózy; Multigene Family; Genomics